(untitled) (Global Journal of Human-Social Science, 2015)
Stress is the psycho-biological construct. Stress creates from the personal behavior and their surrounding environment. Social relationship and organizational environment determines the level of stress among the employee. The study was going to explore the interrelationship between the individual value and collective value with role stress among the Nepal government officer. The study had adopted the simple random sampling to select the respondents. A total 284 government employees from technical and non-technical sectors were selected. Data was taken from the three strata: 1st class, 2nd class and 3rd class officers. The findings showed the significant relationship between the individual and collective values. Mean of individual value was higher than the collective value but the role stress was higher among the officer who took the collective value very much than individual value. Similarly, the non-technical officers felt higher level of stress than the technical officers.